Xanthine oxidase activity and its relation to oxidative stress in human colorectal and prostate cancer - Veljkovic, Andrej; Hadzi-Djokic, Jovan; Stanojevic, Goran; Brankovic, Branko; Basic, Dragoslav; Dinic, Ljubomir; Cvetanovic, Ana; Smelcerovic, Andrija; Sokolovic, Dusan; Kocic, Gordana (Biologia Serbica, 2022)
Colorectal cancer (CRC) and prostate cancer (PC) are the most often diagnosed cancers and the main reason for mortality connected to tumor diseases. There is still a shortage of examination of mechanisms including the influence of xanthine oxidase (XO) activity in progressiveness and invasion of the cancers. Therefore, present study investigated the role of XO activity, in correlation to thiobarbituric acid-reactive substances (TBARS) and advanced oxidation protein products (AOPP), as markers of oxidative stress in progression and invasion of human CRC and PC. We took tissue specimens from 30 patients with CRC and 18 patients with PC, in all four clinical stages of the disease. They were divided in 3 groups: cancer tissue, tissue surrounding the tumor and healthy control tissue group. The activity of XO in tumor tissue and tissue adjacent to the tumor was significantly higher when compared to healthy colon tissue. The highest activity of XO was in T2 and T3 tumor stadiums. TBARS and AOPP also showed higher concentration compared to control healthy tissue. There was a positive correlation between XO activity and prostate specific antigen (PSA) levels in PC. Presented results suggest that one of the possible causes of oxidative stress in CRC and PC could be high XO activity. XO may be involved in the malignant transformation, in the progression and invasion of human CRC and PC. XO could represent a theranostic biomarker, whereas using XO inhibitors such as allopurinol, could be a promising adjuvant therapy.